Disparities in maternal mortality - Phuong Tran; Barbara Jreij; Farideh Sistani; Fadia T. Shaya (Journal of Clinical and Translational Science, 2023)
Maternal mortality rates in the USA remain high, with persistent racial and socioeconomic disparities. We identified 207,016 hospital admissions for pregnant women in Maryland, from 2017 to 2019. Logistic regression was used to identity factors associated with maternal death. The health outcome for black women was more prone to give rise to maternal mortality than for white women. Our study revealed numerous racial and age discrepancies in gestational health outcomes, which opioid use disorder exacerbated. Our findings elaborate on the importance of identifying the drivers of adverse pregnancy outcomes, to help inform policy, and resource allocations.